Factors that influence the recovery of TB patients using Cox proportional hazard regression - ZURNILA MARLI KESUMA; HIZIR SOFYAN; LATIFAH RAHAYU; WARDATUL JANNAH (Jurnal Natural, 2021)
Tuberculosis (TB) is an infectious disease which is one of the biggest health problems in the world, including Indonesia. The government, through the National Tuberculosis Control program, has made various efforts to control tuberculosis. However, this problem was exacerbated by the dramatic increase in the incidence of tuberculosis. This study aimed to determine the Cox proportional hazard regression model and the factors that affect the cure rate of TB patients. We used medical record data for inpatient TB patients for the period July-December 2017 at dr. Zainoel Abidin Hospital. The results showed that with α = 0.1, the factors that influenced the recovery of TB patients were the type of cough, the symptoms of bloody cough and symptoms of sweating at night.  There were 33.93% of patients who did not work. This category included students, domestic helpers, and those who did not work until they suffered from tuberculosis and were treated at dr. Zainoel Abidin Hospital. The hazard ratio (failure ratio) showed that the tendency or cure rate for TB patients who did not experience cough symptoms was 70% greater than patients who experienced phlegm cough symptoms. The cure rate for TB patients who experienced coughing up blood symptoms was 53% greater than patients without these symptoms. The cure rate for TB patients who experienced  symptoms of sweating at night was 54% greater than patients who did not sweat at night.